Membrane fatty acids and physiological disorders in cold-stored ‘Golden Delicious’ apples treated with 1-MCP and calcium chloride - Antunes, Maria Dulce (2022)
The present research intents to study skin fatty acids and physiological disorders developed during cold storage in ‘Golden Delicious’ apples treated with 1-MCP and calcium. Harvested fruits were treated with calcium chloride (Ca), 1-MCP (MCP), Ca + MCP or no treatment (control) and then subjected to cold storage at 0.5 °C for 6 months. Fatty acids’ composition, malondialdehyde (MDA) and the physiological disorders bitter pit (BP), superficial scald and diffuse skin browning (DSB) were measured at harvest and after storage plus 7 days of shelf-life at room temperature ≈22 °C. Palmitic acid decreased and linoleic acid increased over time, while oleic and stearic acids had few changes. Generally, unsaturated/saturated fatty acids and MDA increased over the storage period. Treatment with Ca showed that, at the end of the experiment, the lowest MDA values and the highest unsaturated/saturated fatty acids ratio were mainly due to higher linoleic and lower palmitic acids concentrations, which are coincident with less severe BP. There was no clear correlation between the measured fatty acids (palmitic, linoleic, oleic and stearic), unsaturated-to-saturated fatty acids ratio or MDA with chilling skin physiological disorders. Further research is needed to clarify the changes in membrane properties and the effect of some treatments in response to chilling injury during storage.